2007
DOI: 10.1080/01443610701478991
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health education on reproductive health knowledge among adolescents in a rural Nigerian community

Abstract: This intervention study was to evaluate the impact of reproductive health education on the knowledge and attitude of adolescents in a rural Nigerian community to reproductive health issues. It compared adolescents in a secondary school (study group), which received health education on reproductive health with another secondary school (control group), which did not receive any. The impact of the programme was evaluated with a pre-test baseline knowledge and post-test gain in the knowledge 6 weeks later, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 8 publications
3
29
0
Order By: Relevance
“…Results also indicate that men who learned about FP from CHWs are more likely to be involved in reproductive care which is consistent with the prior studies showing the association between SRH education and positive attitude towards reproductive health behaviour [20, 37]. Bangladesh government has made several programmatic efforts to enhance community-based educational intervention programs to promote maternal and infant health.…”
Section: Discussion and Policy Recommendationssupporting
confidence: 88%
“…Results also indicate that men who learned about FP from CHWs are more likely to be involved in reproductive care which is consistent with the prior studies showing the association between SRH education and positive attitude towards reproductive health behaviour [20, 37]. Bangladesh government has made several programmatic efforts to enhance community-based educational intervention programs to promote maternal and infant health.…”
Section: Discussion and Policy Recommendationssupporting
confidence: 88%
“…Sexual and reproductive health (SRH) knowledge is an important predictor of an individual's sexual behavior and is important health concern and a focus of global attention. Different evidence suggests that even though there is high level of sexual activity in adolescents, there is a limited knowledge of sexual and reproductive health issues among adolescents in different communities; low levels of contraceptive use and negative attitudes toward modern contraceptive methods [5], high pre-marital sex (94.3%) and abortion (88.5%) [6], and Knowledge of more than one contraceptive method was low (39.0%) [7]. In addition, many adolescents have limited knowledge about basic sexually transmitted infections, only 33.3%, 37.9% and 14.5% knew that syphilis, gonorrhea, and hepatitis B, are sexually transmitted diseases [8].…”
Section: Introductionmentioning
confidence: 99%
“…Proper education is not only important to encourage young people to practice safe sex (Orji & Esimai 2005) to prevent unintended pregnancies, but to prevent sexually transmitted infections as well. Some African studies have revealed that intervention studies increase the knowledge of adolescents (Mba et al 2007;Mphatswe et al 2016).…”
Section: Discussionmentioning
confidence: 99%